2019
DOI: 10.3390/polym11122086
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Screening for the Identification of Potential Migrants Present in Polymeric Coatings of Food Cans

Abstract: The coatings used in cans can release complex chemical mixtures into foodstuffs. Therefore, it is important to develop analytical methods for the identification of these potential migrant compounds in packaged food to guarantee the compliance with European food packaging legislation and ensure consumer safety. In the present work, the type of coating in a total of twelve cans collected in Santiago de Compostela (Spain) were evaluated using an ATR (attenuated total reflectance)-FTIR spectrometer. These samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…BPA and its synthesis product BADGE are used for inner coating of canned food, beverage containers, baby bottles and dental composites, and their food contamination is anxious about health hazard (Cabado et al, 2008;Gorecki et al, 2017;Lestido Cardama et al, 2019;Mertens et al, 2016). There are similarities between the two compounds in not only chemical structure but also endocrine disrupting effects and toxicokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…BPA and its synthesis product BADGE are used for inner coating of canned food, beverage containers, baby bottles and dental composites, and their food contamination is anxious about health hazard (Cabado et al, 2008;Gorecki et al, 2017;Lestido Cardama et al, 2019;Mertens et al, 2016). There are similarities between the two compounds in not only chemical structure but also endocrine disrupting effects and toxicokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 listed scientific publications that determined breakdown products in different types of plastic food packaging. Most of the studies reported degradation products as NIAS, and most of the reported NIAS are degradation products from the antioxidants Irganox 1010 and Irgafos 168 [ 59 , 70 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Nias In Plastic Food Packagingmentioning
confidence: 99%
“…Usually, NIAS’s identification requires susceptible advanced analytical techniques and databases and software tools [ 5 , 9 ]. The general workflow for the analysis of FCMs involves the data acquisition after the selection of one or a combination of analytical techniques, such as gas chromatography (GC) for volatile and semi-volatile compounds with low polarity [ 78 , 95 , 123 , 124 , 125 ] and liquid chromatography (LC) for thermally unstable and non-volatile compounds; both coupled with mass spectrometry detectors (MS) [ 28 , 96 , 126 ].…”
Section: The Challenges Of the Nias Assessmentmentioning
confidence: 99%
See 2 more Smart Citations